A grouping of chance coin finds from the time of Mithridates VI Eupator on the territory of the Dnipro Right-Bank Forest-Steppe (in the villages of Moshny, Budysche, and Lozіvok of Cherkasy district, Cherkasy province) - Orlyk , Vasyl (Acta Archaeologica Lodziensia, 2023)
This article suggests that a grouping of stray coin finds containing coins of the Pontic state of Mithridates VI Eupator (120-63 BC), discovered on the territory of the Dnipro River Right-Bank, Forest-Steppe zone (especially near the villages of Moshny-Budyshche-Lozivok, where forty-one coins were found), were deposited due to commercial-monetary rations between the local population and the Greeks. Of course, these relations were not as intensive as in the Greek colonies of the Northern Black Sea. Nevertheless, they provide additional evidence for the picture of economic relations in this region in this period.